A Review on Biomedical Waste Management - Shridhar Shrimant Bagali; Bychapur Siddaiah Gowrishankar; Sachin Shrimant Bagali (Diponegoro University, 2021)
With the growth of healthcare facilities, the amount of biomedical waste produced every day is growing. If biomedical waste management is done correctly, many of the problems can be avoided. Segregation, storage, processing, transportation, and disposal of biomedical waste are all common practices undertaken as part of health care waste management. It involves interdisciplinary relationships in organizational, planning, administrative, financial, engineering, legal, and human resource creation. Medical waste management necessitates dedication from healthcare providers at all levels. The risks and value of their